2018
DOI: 10.1186/s13104-018-3240-x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of workplace violence against physicians in the hospitals, Myanmar

Abstract: ObjectiveWorkplace violence in hospitals is recently becoming a major global concern in many countries. However, in Myanmar, we have felt that patients and their families have rarely made unreasonable complaints in hospitals, and then, the purpose of this study is to report the current state of workplace violence in hospitals in Myanmar. Participants are 196 physicians (108 males and 88 females) in hospitals in Myanmar.ResultsA descriptive survey was conducted in regard to verbal abuse and physical violence fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
8
2
Order By: Relevance
“…The prevalence of physical violence in this study was 4.6%, which was lower than that of previous studies in China6 27 35 36 but still higher than other countries 37. Our study also found high rates of physical violence threats and exposure to Yi Nao.…”
Section: Discussioncontrasting
confidence: 78%
“…The prevalence of physical violence in this study was 4.6%, which was lower than that of previous studies in China6 27 35 36 but still higher than other countries 37. Our study also found high rates of physical violence threats and exposure to Yi Nao.…”
Section: Discussioncontrasting
confidence: 78%
“…Compared to a previous investigation in Myanmar, we found a much higher prevalence of both verbal (47.6%) and physical assault (4.8%) experiences among our sample [8]. These results suggest that, like many other previous studies in LMICs, WPV poses a serious challenge to healthcare workers in Myanmar.…”
Section: Discussioncontrasting
confidence: 69%
“…The prevalence of WPV against healthcare groups around the world has been previously studied, revealing a wide range of reported experiences [6,7]. Only one prior study had reported WPV experiences among physicians in Myanmar, and it had revealed very low rates of both verbal assault (8.7%) and physical assault (1.0%) in the cohort studied [8]. While this study had been large (n = 196) and included respondents from public and private hospitals in three major cities, it had been performed at urban centers using an unvalidated instrument.…”
Section: Introductionmentioning
confidence: 99%
“…24,27 Similar incidents of violent outrage towards doctors have been reported from primary to tertiary care services in Bangladesh, 28 Nepal, 29 Pakistan, 25,30 and Myanmar. 31 As a consequence of these violent outbursts, many health care professionals were brutally injured, and few even lost their lives. 32 India has a high burden of WPV similar to other LMICs.…”
Section: Introductionmentioning
confidence: 99%